A commentary on the quality improvement practices in leading an organizational response to audit feedback. Issue 3 (10th September 2022) - Sykes, Michael
Abstract : Abstract: Clinical audit is commonly used to assess and improve the quality of care. The impact of clinical audit on practice could be improved by supporting the ability of people who receive feedback from audits to mount effective responses. This article, written for people who receive feedback, audit providers and quality improvement leads, describes important practices in the organisational response to feedback. The practices were identified through work to describe the current response to national audit and draw upon theory-informed hypotheses for enhancing audit and feedback. Both the content and implementation of the practices were co-designed with stakeholders and tested alongside different national audits. The identified quality improvement practices provide practical guidance for feedback recipients and enable providers and quality improvement leads to consider the capabilities required for such practices. The approach resonates with organisational readiness to change theory, proposing that informational appraisal and change commitment underpin effective improvement actions.